1989
DOI: 10.2134/agronj1989.00021962008100040010x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Rates of Six Maize Cultivars During Development

Abstract: Production estimates based on photosynthate accumulation are affected by changes in photosynthesis rates related to aging in different cultivars. The influence of leaf and plant age on photosynthetic rates was investigated in six maize (Zea mays L.) cultivars with maturity ratings ranging from <2300 to >3500 CHU (corn heat units). Photosynthesis and irradiance measurements were fitted to rectangular hyperbolas using a nonlinear fitting technique. These curves were analyzed as a function of cultivars, and leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
1
11
0
2
Order By: Relevance
“…A queda de A pode ainda estar relacionada a fatores fisiológicos, como início de senescência, variação da respiração, na eficiência quântica e em gs entre outros (DWYER e Stewart, 1986;STIRLING et al, 1994). Há relatos na literatura de que, sem estresses abióticos, A é maior na fase de floração e/ou de crescimento linear de grãos em relação ao crescimento vegetativo, em função de maior demanda dos drenos (DWYER e STEWART, 1986;DWYER et al, 1989;MACHADO et al, 1994). Também há relatos de que a máxima fotossíntese é atingida ao redor de uma semana após a expansão máxima da folha (DWYER et al, 1989).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A queda de A pode ainda estar relacionada a fatores fisiológicos, como início de senescência, variação da respiração, na eficiência quântica e em gs entre outros (DWYER e Stewart, 1986;STIRLING et al, 1994). Há relatos na literatura de que, sem estresses abióticos, A é maior na fase de floração e/ou de crescimento linear de grãos em relação ao crescimento vegetativo, em função de maior demanda dos drenos (DWYER e STEWART, 1986;DWYER et al, 1989;MACHADO et al, 1994). Também há relatos de que a máxima fotossíntese é atingida ao redor de uma semana após a expansão máxima da folha (DWYER et al, 1989).…”
Section: Introductionunclassified
“…Há relatos na literatura de que, sem estresses abióticos, A é maior na fase de floração e/ou de crescimento linear de grãos em relação ao crescimento vegetativo, em função de maior demanda dos drenos (DWYER e STEWART, 1986;DWYER et al, 1989;MACHADO et al, 1994). Também há relatos de que a máxima fotossíntese é atingida ao redor de uma semana após a expansão máxima da folha (DWYER et al, 1989). No entanto, também há autores que não observam esta resposta (RAWSON et al, 1978).…”
Section: Introductionunclassified
“…(Gimenez et al, 1992). Photosynthesis rate also depends on variety of plant parameters such as genotype, plant stage, leaf age, leaf orientation and position, plant density, and assimilate demand by sink (Dwyer et al, 1989). Differences among genotypes may be due to morphology, resulting in different mesophyll resistances, or they may be explained by the timing and size of carbohydrate requirement of other parts of the plant, particularly the grain (Hunt and van der Poorten, 1985;Hesketh, 1963).…”
Section: Photosynthesis Response and Crop Yieldmentioning
confidence: 99%
“…Bhagsari (1988) reported decreases in net photosynthesis and stomatal conductance with increasing leaf age for sweet potato under field conditions in full sunlight (above 1500 u mole m ^ s'^). Dwyer et al (1989) reported cultiver differences in photosynthèse rates as a function of plant age, and pointed that late-maturing cultivars had higher photosynthetic rates than early-maturing cultivars at comparable growth stages. Pearson et al (1984) observed that the photosynthesis rate for the upper canopy leaves of 85-day-old maize was three to six times higher than for the lower canopy leaves.…”
Section: Photosynthesis Response and Crop Yieldmentioning
confidence: 99%
See 1 more Smart Citation